Mengangkat potensi perempuan: Mendukung kesetaraan gender di berbagai aspek - Hawariyah, Hawariyah (Maliki Interdisciplinary Journal, 2024)
Gender discrimination is a practice that still frequently occurs in everyday life in Indonesia, so various efforts need to be made to support gender equality. In this article, we will discuss developing women’s potential to support gender equality. The results of the study conducted show that there are several forms of efforts that can be made as a form of support for gender equality, namely by 1) providing access for women to education, 2) supporting women’s involvement in the world of work, 3) supporting gender equality in health and reproductive rights , and 4) providing women with access to politics and leadership. It is hoped that these efforts will be a form of support in achieving gender equality. Women must show their potential to contribute in various aspects of life so that they have an equal position with men and are not excluded.